A neuroeconomic theory of obsessive-compulsive disorder - Kaçar, Anıl Şafak; Moustafa, Ahmed A.; Hassan, Mubashir; Zeki, Mustafa; Balcı, Fuat (International journal of neuroscience, 2025)
While there are many studies on the neural bases of obsessive-compulsive disorder (OCD), there is a dire need for a neurocomputational framework to explain its symptoms. To this end, we use the Expected Value of Control (EVC) theory to conceptualize the information processing deficits underlying OCD. Specifically, we argue that when experiencing obsessions, weak cognitive control is favored due to the affective cost of disregarding anxiety-provoking obsessions (akin to ignoring a fire alarm). This affective cost leads to the overvaluation of the cost of cognitive control (deeming it expensive), favoring automatic responses in the form of compulsions. We also exercise other ways by which OCD symptoms can be explained within the same theoretical framework. We ground our EVC-based neuroeconomic account in different neural systems implicated in OCD, including the orbitofrontal cortex, dorsal anterior cingulate cortex (dACC), dorsolateral prefrontal cortex, and basal ganglia, which refer to different EVC constituents. Finally, we argue that input from the bed nucleus of the stria terminalis to dACC introduces the key affective cost information to the estimation of EVC.